Impact of work schedules of senior resident physicians on patient and resident physician safety: nationwide, prospective cohort study - Christopher P Landrigan; Salim Qadri; Jason P Sullivan; Charles A Czeisler; Laura K Barger; Matthew D Weaver (BMJ Medicine)
Objective To determine whether long weekly work hours and shifts of extended duration (≥24 hours) are associated with adverse patient and physician safety outcomes in more senior resident physicians (postgraduate year 2 and above; PGY2+).Design Nationwide, prospective cohort study.Setting United States, conducted over eight academic years (2002-07, 2014-17).Participants 4826 PGY2+ resident physicians who completed 38 702 monthly web based reports of their work hours and patient and resident safety outcomes.Main outcome measures Patient safety outcomes included medical errors, preventable adverse events, and fatal preventable adverse events. Resident physician health and safety outcomes included motor vehicle crashes, near miss crashes, occupational exposures to potentially contaminated blood or other bodily fluids, percutaneous injuries, and attentional failures. Data were analysed with mixed effects regression models that accounted for dependence of repeated measures and controlled for potential confounders.Results Working more than 48 hours per week was associated with an increased risk of self-reported medical errors, preventable adverse events, and fatal preventable adverse events as well as near miss crashes, occupational exposures, percutaneous injuries, and attentional failures (all P<0.001). Working between 60 and 70 hours per week was associated with a more than twice the risk of a medical error (odds ratio 2.36, 95% confidence interval 2.01 to 2.78) and almost three times the risk of preventable adverse events (2.93, 2.04 to 4.23) and fatal preventable adverse events (2.75, 1.23 to 6.12). Working one or more shifts of extended duration in a month while averaging no more than 80 weekly work hours was associated with an 84% increased risk of medical errors (1.84, 1.66 to 2.03), a 51% increased risk of preventable adverse events (1.51, 1.20 to 1.90), and an 85% increased risk of fatal preventable adverse events (1.85, 1.05 to 3.26). Similarly, working one or more shifts of extended duration in a month while averaging no more than 80 weekly work hours also increased the risk of near miss crashes (1.47, 1.32 to 1.63) and occupational exposures (1.17, 1.02 to 1.33).Conclusions These results indicate that exceeding 48 weekly work hours or working shifts of extended duration endangers even experienced (ie, PGY2+) resident physicians and their patients. These data suggest that regulatory bodies in the US and elsewhere should consider lowering weekly work hour limits, as the European Union has done, and eliminating shifts of extended duration to protect the more than 150 000 physicians training in the US and their patients.